Pengembangan Desain dan Diferensiasi Produk sebagai Keunggulan Kompetitif pada Bisnis Ritel UMKM Furnitur dan Aksesoris Interior Rumah - Titi Indahyani (Humaniora, 2012)
Trade globalization caused the overwhelming of overseas products in the center of trades in Indonesia. The effect of this case was the small-scale and middle industries’ products were difficult to compete with the impor one in Indonesia. The lack of product development strategy, lack of people’s skils, technology, and dependence on the imported raw materials caused the limitation of stock production which was unique, creative, and innovative that became the competitve advantage of the UMKM. Based on these problems, a research to consider a strategy priority that was appropriate, effective, and efficient was conducted.